2019
DOI: 10.1111/jam.14446
|View full text |Cite
|
Sign up to set email alerts
|

Methylsulfonylmethane exhibits bacteriostatic inhibition of Escherichia coli , and Salmonella enterica Kinshasa, in vitro

Abstract: Aims To evaluate antibacterial properties of methylsulfonylmethane (MSM) on Escherichia coli (MDRE21) and Salmonella enterica serovar Kinshasa (SK132). Methods and Results Bacterial proliferation analysis was measured spectrophotometrically during log phase growth with 0, 3, 5, 7, 10, 12 and 16% MSM. To assess the mechanism of inhibition, cultures were grown overnight with 0–16% MSM and enumerated on unmedicated brain–heart infusion agar (BHIA) or BHIA with 0–16% MSM. The long‐term viability studies were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…However, a clear explanation of the MSM-mediated improvement in ileal morphology is not available. In earlier studies, MSM was shown to exhibit antimicrobial activity or immunemodulating activity [27,35]. However, the finding that dietary MSM did not affect ileal SCFAs in this study suggests that the antimicrobial activity of MSM might not be responsible for MSM-mediated improvement in ileal morphology.…”
Section: Discussioncontrasting
confidence: 72%
“…However, a clear explanation of the MSM-mediated improvement in ileal morphology is not available. In earlier studies, MSM was shown to exhibit antimicrobial activity or immunemodulating activity [27,35]. However, the finding that dietary MSM did not affect ileal SCFAs in this study suggests that the antimicrobial activity of MSM might not be responsible for MSM-mediated improvement in ileal morphology.…”
Section: Discussioncontrasting
confidence: 72%
“…It has been well reported that dietary MSM plays an important role in reducing oxidative stress [12,15], inhibiting pathogenic bacteria [30], and improving the host's immune response [31]. In addition, MSM is known to inhibit the cortisol-induced stress response in horse skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The structure and functionality of the intestinal microbiota are crucial for the health of poultry. Due to the antimicrobial activities of MSM [ 43 ] and SS [ 44 ], it is expected that their supplementation in the diets of laying hens could balance gut microbiota and improve gut health, which prompted us to measure ileal morphology and ileal SCFAs. Both MSM and SS did not affect ileal SCFAs, but increased villus height and crypt depth ratio, the indicator of gut function and health [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%